INVESTIGATION OF FOOD POISONING OUTBREAK IN A TEMPORARY CAMP USING MIXED METHODOLOGY APPROACH - SR, MANJUNATH; RAVISHEKAR N, HIREMATH; VISWANATH, KASI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: In the present study, a food poisoning outbreak was reported from a medical officer in-charge of the temporary camp, where a largegathering of around 400 boys and girls had consumed meal from a common kitchen during training event. Thus, the main objective of the study was to investigate the outbreak and institute preventive measures. Methods: The camps had a total strength of 400. Ten individuals reported with history of vomiting and diarrhea. Mixed methodology approach was used to carry out epidemiological investigation. Inspection of cookhouse and surroundings was carried out. Results: Ten individuals were affected. A short incubation period ranging from 4 to 6 h with median incubation of 5 h. Among cases, all had diarrhea with the number of episodes ranging from 3 to 5. Seven patients had vomiting (70%), two (20%) patients had blood in stools, and none reported with abdominal cramps and fever. A total of five food items were suspected for food poisoning. However, none had a significant association with outcome. In depth interview and descriptive analysis revealed that mayonnaise in sandwich was the cause for food poisoning. Conclusion: Food poisoning outbreak is a common occurrence now days. Hygiene and sanitation of cookhouse to be carried out routinely to prevent outbreak. Individuals in camps should also be educated of 5 Key points of food safety by the WHO.